QuickBooks 2009 on demand - Perry, Gail A. (On demand (Indianapolis, Ind.), 2009)
Need answers quickly? QuickBooks® 2009 on Demand provides those answers in a visual step-by-step format. We will show you exactly what to do through lots of full color illustrations and easy-to-follow instructions. Produce and customize reports that show exactly how your company is doing Schedule transactions so you'll never forget a due date again Bill time and expenses directly to customers Use the new QuickBooks features for 2009, including a redesigned Payroll Center and the new Accountant's Copy that lets you keep working while your accountant reviews your books Create and use a budget Reconcile your bank account to the penny without waiting for the bank statement to come in the mail Keep detailed records of fixed asset acquisitions Protect financial information with the latest in security techniques Send customized mailings to your customers and vendors Learn tips and shortcuts to help make your QuickBooks experience more efficient and to customize your program to fit your style Process transactions the right way by following the accounting rules interspersed throughout the book Introduction xv Chapter 1: Setting Up Your Company with the EasyStep Interview 1 Chapter 2: Setting Up and Using Payroll Features 27 Chapter 3: Adding or Changing Information After the Interview Is Completed 69 Chapter 4: Invoicing and Collecting Income 107 Chapter 5: Making Purchases and Recording Payments 141 Chapter 6: Collecting and Paying Sales Tax 171 Chapter 7: Using Time-Saving Features 185 Chapter 8: Job Cost Estimating and Tracking 199 Chapter 9: Tracking Time 219 Chapter 10: QuickBooks Tips and Tricks 237 Chapter 11: Using the QuickBooks Online Features 263 Chapter 12: Preparing Income Tax Returns 295 Chapter 13: Security 309 Chapter 14: Using Inventory Features 328 Chapter 15: Recording Your Assets 349 Chapter 16: Recording Owners' Equity 363 Chapter 17: Recording Liabilities 371 Chapter 18: Preparing the Top Ten QuickBooks Reports 387 Workshops 411 Index 423.